국내외 큐브위성 운용 사례로 살펴본 교훈과 대책 - 구인회; 이명규; 박설현; In-Hoi Koo; Myung-Kyu Lee; Seul-Hyun Park (우주기술과 응용, 2023)
As the need for low-cost, high-efficiency cubesats develops in the new space age, commercial paradigms are shifting in the private sector. This paper examines the challenges of launching and operating both domestic and foreign cubesats, and proposes practical solutions to ensure the robustness and reliability of the satellites from a practical perspective. In particular, the paper deals with checkpoints that are easy to miss, focusing on key events that can occur from the satellite deployment process through normal mode to mission mode in the operation scenario. Although the contents presented in this paper may not be technically applicable to all cubesat systems due to the different nature of each satellite bus system, they will be of some help during satellite assembly, integration and testing. 민간 주도의 상업적 목표가 최우선 과제가 된 뉴 스페이스 시대에 이르러 낮은 투자 비용 대비 높은 효율을 가진 큐브위성이 시대적 상황과 결합되면서 수요가 폭발적으로 증가하고 있다. 따라서 본 논문에서는 국내 및 해외의 큐브위성 발사와 운영사례를 통해 밝혀진 문제점들 살펴보고 실무적인 관점에서 위성의 강건성과 신뢰성을 확보하는 방안에 대해서 제시하였다. 특히 위성의 사출 과정에서부터 임무 시나리오 상정상모드나 임무모드 이전 단계까지 발생되는 주요 이벤트를 중심으로 놓치기 쉬운 점검 사항들에 대해 중점적으로 다루었다. 다만, 논문에 제시된 내용은 위성 버스 시스템의 특성에 따라 기술적으로 적용할 수 없거나 상이한 측면이 있을 수 있다. 하지만, 위성의 운용 과정에서 충분히 발생 가능한 개연성 높은 문제점을 중심으로 기술하였기 때문에 위성의 조립·통합·테스트 과정에서 해당 내용이 작은 도움이 될 수 있을 것으로 판단된다.